Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Edit: I just rewrote the whole question, to make it clear, what I'm looking for. Originally I asked about solving $16^{x+1} = 4^{x+3}$, then corrected it to $16^{x+2} = 4^{x+3}$.

But what I really want to know is this: How do you get from

$$(x + 2)\ln(16) - (x + 3)\ln(4) = \ln(1)$$


$$x = \frac{3\ln(4) - 2\ln(16)}{\ln(16) - \ln(4)}$$

I'm particularly concerned about the factors $(x+2)$ and $(x+3)$ as I don't understand, how they lead up the the last term above.

share|cite|improve this question
Multiply everything out, then group any term with an $x$. Remember than $\ln 1 = 0$. – Antonio Vargas May 17 '12 at 22:31
You know that $(x+1)\ln 16 = x\ln 16 + 1\ln 16$, right? – Rahul May 17 '12 at 22:39
Why are you using logarithm ? However if you want to use it in a appropriated basis. – checkmath May 17 '12 at 22:39
Because I'm learning how to calculate with logarithms. – Miroslav Cetojevic May 17 '12 at 22:40
If you edit the question to make a correction, please mention that you've done so in the question, so that people understand why the answers are all now wrong. – Ben Millwood May 17 '12 at 23:16
up vote 2 down vote accepted

Once you've got $(x+2)\ln(16)−(x+3)\ln(4)=\ln(1)$, use $\log 1 = 0$ (true regardless of the base) and then forget about the logs entirely for now: the rest is just algebra, so let $a = \ln(16)$ and $b = \ln(4)$. Then solve $$(x+2)a - (x+3)b = 0$$ for $x$, by expanding the brackets and rearranging; you will get $$x = \frac{3b - 2a}{a - b}$$, which is indeed (substituting back in $a$ and $b$) exactly what you wanted.

(If you can't do the algebra, say so and I'll give a bit more detail).

share|cite|improve this answer
Ah, now it makes sense. I got too focused on the logs and somehow fumbled over the whole equation. – Miroslav Cetojevic May 17 '12 at 23:35

Why would you apply logarithms before simplifying stuff??

$16^{x+1}=4^{x+3}\Longrightarrow \left((2^4)\right)^{x+1}=\left(2^2\right)^{x+3}\Longrightarrow 2^{4x+4}=2^{2x+6}\Longrightarrow 4x+4=2x+6\Longrightarrow x=1$

share|cite|improve this answer
Well, uh, it's about learning logarithms. The solution of $x$ was marked as $-1$, is this wrong? – Miroslav Cetojevic May 17 '12 at 22:37
@MiroslavCetojevic Yes $x=-1$ is indeed wrong. You can check this by plugging in the value $x=-1$ to get the incorrect statement that $16^{-1+1} = 4^{-1+3}$ – user17762 May 17 '12 at 22:52
Of course it is wrong! $,1=16^0=16^{-1+1}\neq 4^{-1+2}=4^2=16$ – DonAntonio May 17 '12 at 22:52
Ah, shit, I put in the wrong number! It's supposed to be $x+2$. – Miroslav Cetojevic May 17 '12 at 22:57

To proceed with what you have done, you need to recognize that $\ln(1) = 0$ and $\ln(a^b) = b \times \ln(a)$ i.e. $\ln(16) = \ln(4^2) = 2 \ln(4)$. Then you can simplify the expression you have to get $$(x+2) \times 2 \times \ln(4) - (x+3) \times \ln(4) = 0$$ i.e. \begin{align*} (x+2) \times 2 \times \ln(4) &= (x+3) \times \ln(4) \\ 2(x+2) &= x+3 \\ 2x+4 &= x +3 \\ x&=-1 \end{align*}

The easier way is to take the logarithm to the base $4$. Then we get that $$(x+2) \times \log_4(16) = (x+3) \times \log_4(4)$$ Hence, \begin{align*} (x+2) \times \log_4(4^2) &= (x+3) \times 1 \\ (x+2) \times 2 \times \log_4(4) &= (x+3) \times 1 \\ (x+2) \times 2 \times 1 &= (x+3) \times 1 \\ 2x+4 &= x+3 \\ x&=-1 \end{align*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.